Percutaneous Retrieval of Embolized Catheter Fragments from Preterm Newborn to Adult: A Single-Center Experience for 10 Years - Aydın Şahin, Derya; Temel, Münevver Tuğba; Başpınar, Osman (European Journal of Therapeutics, 2023)
Objective: Umbilical vein catheterization and central venous catheters are frequently used. We aimed to present our experiences in 15 of 16 patients with embolized catheters who were successfully retrieved by percutaneous intervention. Methods: During 10 years, 16 patients with embolized umbilical vein catheters, port catheters, central venous catheters, catheter fragments, and guide wires were examined. Demographic characteristics of the patients, catheter indications, embolized catheter types, localizations and lengths of a catheter, durations of flora, entry points during retrieval of embolized catheters, snare’s features used, grasping location of the embolized catheter, and additional procedures were examined retrospectively. Results: Of the 16 patients, 7 were girls; their ages were between 11 days and 39 years; 14 of the patients were children. Their weights were between 1.3 kg and 65 kg. The umbilical vein catheter in 5 patients, the port catheter in 7 patients, a double-lumen central venous catheter in 1 patient, the distal part of the fragmented sheath in 1 patient, and the guide wire in 2 patients were embolized. Conclusions: The procedures of umbilical vein catheterization, peripheral central vein catheterization, and port catheterization are safe in experienced hands. Rarely, those catheters may break and embolize. As soon as it is diagnosed, embolized catheters should be removed to prevent complications. Since the retrieval of embolized catheters by percutaneous transcatheter route is safe and successful, it should be used as the first choice.